Annealing effect on SiNx/SiO2 superlattice with ultrathin sublayer fabricated using plasma-enhanced atomic layer deposition. Issue 15 (1st August 2022) - Ma, Hong-Ping; Gu, Lin; Shen, Yi; Huang, Wei; Liu, Yu-Hang; Zhu, Jing-Tao; Zhang, Qing-Chun
Abstract: Because of the precise control of film thickness, atomic layer deposition (ALD) offers significant advantages in fabricating high-quality superlattice films. For the first time, a SiNx /SiO2 superlattice with an ultrathin SiNx sublayer layer (1.5 nm) and a SiO2 barrier layer (3 nm) was successfully fabricated using plasma-enhanced ALD. Transmission electron microscopy (TEM) measurements demonstrate the maintenance of multilayer structures with smooth interfaces. Next, the annealing effect on the microstructural, optical, and chemical properties of these SiNx /SiO2 superlattice structures was thoroughly investigated. With increasing annealing temperature, X-ray reflection (XRR) and TEM measurements revealed consistent changes in interface, morphology, roughness, density, and thickness. After high-temperature annealing, Fourier-transform infrared spectroscopy (FTIR) measurements combined with X-ray photoelectron spectroscopy (XPS) measurements revealed significant reductions in Si–H-related defects and absorption bands. Photoluminescence (PL) was used to characterize the light emission property, and it was discovered that increasing the annealing temperature decreased the PL peak intensity at ∼550 and 900 nm. The silicon nanocrystals (Si–NCs)-related PL peak (∼900 nm) became dominant as the annealing temperature increased. The findings in this paper shed light on the annealing effect on the new superlattice material prepared via ALD. Improved PL properties of this type of superlattice are expected and can be obtained in future research by optimizing the ALD deposition process and annealing parameters.